2022
DOI: 10.1080/21655979.2022.2073126
|View full text |Cite
|
Sign up to set email alerts
|

Noise exposure and its relationship with postinfarction cardiac remodeling: implications for NLRP3 inflammasome activation

Abstract: In recent years, high-decibel noise has emerged as a causative risk factor for ischemic heart disease. Massive noise overdose is associated with increased endocrine, neural, and immune stress responses. The NLRP3 (nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain containing 3) inflammasome, the most characterized supramolecular complex and a potent mediator of inflammatory signaling, has been reported to be a marker of increased ischemic heart disease vulnerability. Our study eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The presented JEMs have already been used in several studies ( Eriksson et al 2018 ; Enoksson Wallas et al , 2019 ; Wallas et al 2018 , 2019 , 2020 ; Aarhus et al 2020 ; Eriksson et al 2021 ; Lissaker et al 2021 ; Thacher et al 2022 ) to study health effects from noise exposure such as cortisol levels, asthma, birth outcomes, and cardiovascular disease. We anticipate further use as an increasing number of epidemiological studies has shown health effects as a result of long-term exposure to noise ( An et al 2018 ; Kerns et al 2018 ; Brauner et al 2019 ; Liu et al 2022 ; Wei et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presented JEMs have already been used in several studies ( Eriksson et al 2018 ; Enoksson Wallas et al , 2019 ; Wallas et al 2018 , 2019 , 2020 ; Aarhus et al 2020 ; Eriksson et al 2021 ; Lissaker et al 2021 ; Thacher et al 2022 ) to study health effects from noise exposure such as cortisol levels, asthma, birth outcomes, and cardiovascular disease. We anticipate further use as an increasing number of epidemiological studies has shown health effects as a result of long-term exposure to noise ( An et al 2018 ; Kerns et al 2018 ; Brauner et al 2019 ; Liu et al 2022 ; Wei et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In vivo programmed electrical stimulation was performed as previously described. [ 22 ] In brief, the chest of the rat was opened to expose the heart after anaesthetization. Then, a recording electrode and a stimulating electrode were used to record the monophasic action potentials (MAPs) from the basal surface of the infarcted‐BZ.…”
Section: Methodsmentioning
confidence: 99%